Pengaruh Pertumbuhan Aset, Profitabilitas dan Likuiditas Terhadap Struktur Modal pada Perusahaan Manufaktur Sub Sektor Makanan & Minuman yang Terdaftar Di Bursa Efek Indonesia Periode (2016-2020) - Ratna Dwi Astuti; Gendro Wiyono; Risal Rinofah (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to analyze the effect of asset growth, profitability and liquidity on the capital structure of manufacturing companies listed on the IDX. This type of research is quantitative research. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Samples were taken from 17 companies in 2016-2020. The sampling technique used purposive sampling method. The data is obtained and downloaded through the website www.idx.co.id and the company's website. Data analysis used descriptive analysis, classical assumption test, regression analysis, hypothesis testing and coefficient of determination test. The results of this study indicate that Asset Growth (AG) has no effect on capital structure (DER), Profitability (ROE) has an effect on capital structure, Liquidity (CR) has an effect on capital structure (DER), AG, ROE, and CR simultaneously have a significant effect against DERs.